MENGENAL KAJIAN LANSKAP LINGUISTIK DN UPAYA PENATAANNYA DALAM RUANG-RUANG PUBLIK DI INDONESIA - Dany Ardhian; Soemarlam Soemarlam (Jurnal Akrab Juara, 2018)
The texts displayed in the public sphere either static text or mobile text are a sign of social activity in progress and work. The dominance of the choice of certain language codes and the script used is a symbol of the social dominance of certain groups in the society. The linguistic landscape is a study that investigates texts in the public sphere in order to analyze the factors of language and social factors that exist. This study also served to analyze social phenomena in the community due to social activities. The study also looks at how language contests and competes in public areas. The more varied and tangled the texts are on display, there needs to be structuring by the government as a stakeholder. The arrangement is in the form of four considerations: (1) language revitalization in the effort of language defense, (2) education through text messages, (3) text that is explicitly sanctioned using more persuasive and targeted language (not carelessly displayed); and (4) government presence in the choice of language settings so that language issues have no impact on social conflicts Keyword: Linguistics Lanscape, language revitalization, language maintenance, public space